2018
DOI: 10.1016/j.disc.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

The Möbius function of permutations with an indecomposable lower bound

Abstract: We show that the Möbius function of an interval in a permutation poset where the lower bound is sum (resp. skew) indecomposable depends solely on the sum (resp. skew) indecomposable permutations contained in the upper bound, and that this can simplify the calculation of the Möbius sum. For increasing oscillations, we give a recursion for the Möbius sum which only involves evaluating simple inequalities.Our motivation for this paper is to find a contributing set C σ,π that is significantly smaller than the pose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This example, pointed out by Smith [15], gave the largest previously known growth of |µ(1, π)| in terms of |π|. We note that Brignall and Marchant [5] have recently found another, substantially different example of a family of permutations π for which they conjecture that |µ(1, π)| is quadratic in |π|.…”
Section: Descents and Inverse Descentsmentioning
confidence: 63%
“…This example, pointed out by Smith [15], gave the largest previously known growth of |µ(1, π)| in terms of |π|. We note that Brignall and Marchant [5] have recently found another, substantially different example of a family of permutations π for which they conjecture that |µ(1, π)| is quadratic in |π|.…”
Section: Descents and Inverse Descentsmentioning
confidence: 63%
“…These are well-known consequences of Propositions 1 and 2 of Burstein, Jelínek, Jelínková and Steingrímsson [4], and we refrain from providing proofs here. The reader is directed to Lemma 4 in [3] for a proof of Lemma 1. Lemma 2 is a trivial extension of Corollary 3 in [4].…”
Section: We Now Havementioning
confidence: 99%
“…There are cases where we can determine that the principal Möbius function of a permutation is zero by examining part of the permutation, but the permutation is not strongly zero. As an example, if a permutation π, with |π| > 2, begins 12, then as a consequence of Propositions 1 and 2 in Burstein, Jelínek, Jelínková and Steingrímsson [5] (first stated explicitly as Lemma 4 in Brignall and Marchant [4]), µ[π] = 0. Such a permutation is not strongly zero, since 12 ∈ SZ.…”
Section: Permutations Containing a Specific Intervalmentioning
confidence: 99%
“…Brignall and Marchant [4] showed that if the lower bound of an interval is indecomposable, then the Möbius function depends only on the indecomposable permutations contained in the upper bound, and used this result to find a fast polynomial algorithm for finding µ[π] where π is an increasing oscillation.…”
Section: Introductionmentioning
confidence: 99%